DYNAMICS OF PINE ENGRAVER BEETLE-CAUSED FOREST DECLINE IN TETERIVSKE FORESTRY ENTERPRISE - Meshkova, V. L.; Borysenko, O. I. (Forestry and Forest Melioration, 2018)
Introduction The area of pine forest decline has been increasing for the last decades in many European countries including Ukraine. The trees weakened by drought or other unfavorable conditions are successfully attacked by stem pests. Ecological conditions of last decades become favorable for pine engraver beetle Ips acuminatus (Gyllenhal, 1827), which inhabits the branches and treetops, develops in several generations per year, including sister broods. Therefore it attacks the trees almost permanently from May to the end of August. In Ukraine, phenology and occurrence of Ips acuminatus were studied in the Steppe and Forest Steppe zones. The aim of this work was the revealing the peculiarities of forest decline in the Scots pine (Pinus sylvestris L.) stand infested by pine engraver beetle using as example Teterivske Forestry Enterprise. Materials and Methods The research was carried out in 2014–2017 in the stands of Scots pine in the Teterivske Forestry Enterprise (Kiev region). Dynamics of forest decline was studied on the base of monitoring data of forest health condition and of selective and clear sanitary felling in the stands. Data on forest fund, especially on pine stands area, were taken from forest inventory database as of 2016. Meteorological parameters (air temperature and precipitation) were taken from meteorological station Teteriv (50?41’54" N; 29?35’57" E). The dates of stable temperature transition over 0, 5 and 10°C have been calculated using MS Excel applications. Spatial analysis of forest decline “spots” was carried out using QGIS 2.18. Linear trend (R2) and Spearman’s rank correlation coefficient (r) were calculated by a standard approach using MS Excel. Results and Conclusions Analysis of declining pine stands infested by pine engraver beetle in Teterivske Forestry Enterprise for 2001–2017 shows increase infested area since 2009 with the maximum of selective sanitary felling area in 2013 and clear sanitary felling area in 2016. After 2013, the total timber volume obtained from clear and selective sanitary felling, as well as timber volume per hectare, has noticeably increased. Timber volume from selective sanitary felling in 2011–2015 and 2016–2017 exceeded the average value for 2001–2017 by 35.9 and 68 %, or by 1.4 and 1.7 times respectively. A negative correlation was found between the area of clear sanitary felling and the date of stable air temperature transition over 0°C in spring, as well as between the area of clear sanitary felling and precipitation during vegetation period. Several stages of increasing the area of forest decline were registered during vegetation period of 2014–2016. Selective felling was not able to stop forest decline. Selective sanitary felling was 2–3 times repeated in the same forest plots for 2014–2017. In 2017 clear sanitary felling was carried out in the 28.6 % of plots with previous selective sanitary felling. 8 Figs., 1 Table, 14 Refs.